Monomethyl Auristatin E, a Potent Cytotoxic Payload for Development of Antibody-Drug Conjugates against Breast Cancer - Abdollahpour-alitappeh, Meghdad; Amanzadeh, Amir; Heidarnejad, Fatemeh; Habibi-Anbouhi, Mahdi; Lotfinia, Majid; Razavi-vakhshourpour, Sepand; Jahandideh, Saeed; Najminejad, Hamid; Balalaie, Saeed; Abolhassani, Mohsen (Novelty in Biomedicine, 2017)
Background: Breast cancer is a heterogeneous disease characterized by differential responses to targeted and chemotherapeutic agents. Antibody-drug conjugates are one of the promising strategies for the treatment of breast cancer. Monomethyl auristatin E (MMAE) is a highly potent microtubule inhibitor and a common payload used for development of antibody-drug conjugates. The purpose of this study was to investigate the cytotoxic effects of MMAE on breast cancer cell lines. Materials and Methods: MDA-MB-468 and MDA-MB-453 cells were treated with MMAE at various concentrations (1, 10, 100, and 1000 ng/ml), and cytotoxicity was measured after 48 and 72 hours using an MTT assay. Results: Our findings indicated that MMAE possesses dose- and time-dependent cytotoxic activities against human breast cancer cells. The morphological features of the treated cells were supportive of the cytotoxic activity of MMAE. The results of the MTT assay showed that MMAE has a significant cytotoxicity against MDA-MB-468 and, to a lesser degree, MDA-MB-453 cells. Conclusion: MMAE can be used as a highly cytotoxic payload for development of antibody-drug conjugates against breast cancer.